Pembelajaran Matematika Berbasis Proyek Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SMA Kelas XI - Rizka Maulidatun Nadifah; Rahayu Nugraheni; Ubaidillah Aisy Kodir; Nur Wiji Sholikin (FKIP UNSULTRA, 2026)
Mathematical problem-solving ability is one of the important competencies that high school students, especially grade XI students, must have to face the demands of 21st-century learning. However, mathematics learning in schools still tends to be oriented towards memorizing formulas and solving routine problems, so that students' problem-solving abilities have not developed optimally. This study aims to determine the effectiveness of project-based mathematics learning (PBL) in improving mathematical problem-solving abilities of grade XI high school students. This study used a qualitative approach with an explanatory sequential design. The subjects were 30 grade XI high school students. Data collection was carried out through pre-tests and post-tests, observations, questionnaires, interviews, and documentation. Quantitative data analysis was carried out using t-tests and N-Gain Scores, while qualitative data were analyzed descriptively through data triangulation. The results showed that project-based mathematics learning was able to significantly improve students' mathematical problem-solving abilities. Students became more active in understanding problems, planning solution strategies, carrying out calculations, and evaluating results. In addition, project-based learning also increased students' independence, creativity, cooperation, and motivation towards learning mathematics. Although there were still challenges in time management and group assignments, overall, project-based mathematics learning proved effective and could be used as an alternative learning strategy to improve the mathematical problem-solving skills of eleventh-grade high school students.